The Influence of Openness to Experience, Entrepreneurial Knowledge, and Digital Literacy on the Interest in Entrepreneurship among Generation Z in the Special Region of Yogyakarta - Sazkia Lutfi Anggitia; Ema Nurmaya; Ani Muttaqiyatun; Suryana Hendrawan (The Indonesian Institute of Science and Technology Research, 2026)
Entrepreneurship is one of the efforts to reduce unemployment and improve the economy in Indonesia. Compared to other countries, interest in entrepreneurship in Indonesia is still relatively low. Therefore, the government has made Generation Z a top priority to increase interest in entrepreneurship. This study aims to determine the influence of openness to experience, entrepreneurial knowledge, and digital literacy on the interest in entrepreneurship among Generation Z in the Special Region of Yogyakarta. The population in this study was all Generation Z in the Special Region of Yogyakarta, with a sample of 207 Generation Z respondents residing in the region. This study was conducted using quantitative methods with primary data obtained from questionnaires distributed via Google Forms and measured using a Likert scale. This study used non-probability sampling with purposive sampling techniques. This research was processed using SPSS version 22. The data analysis techniques in this study used validity and reliability instrument tests, multiple linear regression analysis, t-tests, F-tests, and determination coefficients. The results of this study indicate that openness to experience and entrepreneurial knowledge partially have a positive and significant effect on the entrepreneurial interest of Generation Z. Meanwhile, digital literacy does not affect the entrepreneurial interest of Generation Z.